2020
DOI: 10.1093/ageing/afaa090
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic drugs and incident dementia, mild cognitive impairment and cognitive decline: a meta-analysis

Abstract: Background the long-term effect of the use of drugs with anticholinergic activity on cognitive function remains unclear. Methods we conducted a systematic review and meta-analysis of the relationship between anticholinergic drugs and risk of dementia, mild cognitive impairment (MCI) and cognitive decline in the older population. We identified studies published between January 2002 and April 2018 with ≥12 weeks follow-up betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 30 publications
1
57
0
1
Order By: Relevance
“…We quantified the effects of anticholinergic medications on cognition in children systematically across the literature. We report that, unlike older adult samples [7][8][9] , anticholinergic medications are not associated with cognitive impairments in children. This finding was regardless of the classification approach used: drug class, potency, duration of use, and cognitive domain.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…We quantified the effects of anticholinergic medications on cognition in children systematically across the literature. We report that, unlike older adult samples [7][8][9] , anticholinergic medications are not associated with cognitive impairments in children. This finding was regardless of the classification approach used: drug class, potency, duration of use, and cognitive domain.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, all study designs included in this review were experimental, whereas those included in reviews of older adults are typically longitudinal epidemiological cohort studies [7][8][9] . Standards of reporting cognitive www.nature.com/scientificreports/ performance also differ between children and adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2017; Pieper et al . 2020), the latter being associated with high anticholinergic burden 15–20 years before diagnosis (Richardson et al . 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Further to general prescribing guidelines 1,2 which caution against anticholinergic medication use in older adults, two academic groups (5th Canadian Consensus Conference on the Diagnosis and Treatment of Dementia 3 and the Lancet Commission 4 ) have recently identified anticholinergic medications among potential risk factors for developing dementia. Subsequent to the publication of these guidelines, several new studies have identified exposure to anticholinergic agents as risk factors for mild cognitive impairment and dementia 5–7 . Clinical experience and research demonstrate an increased risk of adverse drug events, 8–12 cognitive impairment, 13–18 and mortality 12 related to the use of anticholinergic drugs in older adults.…”
Section: Introductionmentioning
confidence: 99%